2011
DOI: 10.1103/physrevlett.106.050402
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Pairing and Ferromagnetic Instabilities in Ultracold Fermi Gases near Feshbach Resonances

Abstract: We study the quench dynamics of a two-component ultracold Fermi gas from the weak into the strong interaction regime, where the short time dynamics are governed by the exponential growth rate of unstable collective modes. We obtain an effective interaction that takes into account both Pauli blocking and the energy dependence of the scattering amplitude near a Feshbach resonance. Using this interaction we analyze the competing instabilities towards Stoner ferromagnetism and pairing.Ferromagnetism in itinerant F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
193
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(210 citation statements)
references
References 28 publications
13
193
4
Order By: Relevance
“…In practice, for ultracold gases, the repulsive branch at positive scattering lengths is only metastable. Therefore, a calculation of the energy on this branch alone is not sufficient to determine the conditions for ferromagnetism at least as a metastable state [44]. For example, a variational calculation of the energy of a single flipped spin in the background of a fully polarized up-spin Fermi sea with wave vector k F ↑ indicates that the fully polarized state is stable if k F ↑ a > 2.35 [20].…”
Section: Absence Of Ferromagnetism For Zero Range Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, for ultracold gases, the repulsive branch at positive scattering lengths is only metastable. Therefore, a calculation of the energy on this branch alone is not sufficient to determine the conditions for ferromagnetism at least as a metastable state [44]. For example, a variational calculation of the energy of a single flipped spin in the background of a fully polarized up-spin Fermi sea with wave vector k F ↑ indicates that the fully polarized state is stable if k F ↑ a > 2.35 [20].…”
Section: Absence Of Ferromagnetism For Zero Range Interactionsmentioning
confidence: 99%
“…In the experiment [19], the gas is initially prepared in the weakly interacting limit k F a ≪ 1 and then the interactions are quickly ramped to the strongly repulsive regime k F a ≫ 1 in order to avoid production of bound dimers [43]. An analysis of the dynamic competition between a putative formation of ferromagnetic domains within an RPA-approximation and the formation of pairs indicates that the growth rate of the latter instability is always faster [44]. In particular, as shown by these authors, anomalies of the kind seen experimentally can be explained in terms of pair formation rather than incipient ferromagnetism (see also [45]).…”
Section: Absence Of Ferromagnetism For Zero Range Interactionsmentioning
confidence: 99%
“…as to why the repulsive Fermi gas in a 3D homogenous system is unstable close to Feshbach resonance [29][30][31]. For instance, the instability has been attributed to the shifted resonance in the background of a Fermi sea [29], the pairing instability dominating over ferromagnetism instability [30], or the vanishing zero-momentum molecule due to Pauli-blocking effect of Fermi-sea atoms [31].…”
Section: Stability Of Repulsive Fermi Gases In Trapped Geometriesmentioning
confidence: 99%
“…For instance, the instability has been attributed to the shifted resonance in the background of a Fermi sea [29], the pairing instability dominating over ferromagnetism instability [30], or the vanishing zero-momentum molecule due to Pauli-blocking effect of Fermi-sea atoms [31]. All these studies can lead to the same conclusion at low temperatures, i.e., the 3D Fermi gas becomes unstable at the place where a s is comparable to the inter-particle distance (1/k F ), or equivalently, the two-body binding energy (E b ∼ 1/ma 2 s ) is comparable to the Fermi energy (E F ∼ k 2 F /m).…”
Section: Stability Of Repulsive Fermi Gases In Trapped Geometriesmentioning
confidence: 99%
“…Our spectroscopic approach has confirmed the existence of the predicted repulsive branch [9,12,13] and has demonstrated that the repulsive polaron can exist as a well-defined quasiparticle even deep in the strongly interacting regime. The long lifetime of the repulsive polaron in our system, which we ascribe to the finite effective range of the interparticle interaction, may be a key factor to overcome the problem of decay into molecular excitations [11,19] in the experimental investigation of metastable many-body states that rely on repulsive interactions. In particular, the creation of states with two fermionic components phase-separating on microscopic or macroscopic scales [5][6][7][8]10, 11] appears to be an intriguing near-future prospect.…”
mentioning
confidence: 99%